Produção de sabonetes sólidos com óleo usado e essência de cravo-da-índia - Marchezan, Mariana dos Santos Peres Reck; Rondon, Josimara Nolasco; Otsubo, Helena de Cassia Brassaloti; Thomazelli Junior, Ismael; Ítavo, Luis Carlos Vinhas; Peruca, Ricardo Dias; Souza, Antonio Pancracio de; Fabri, Joao Roberto (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The objective of this study was to promote the reuse of waste oil for the production of solid soap with the essence of as indian clove, putting into practice the sustainability and preservation of the environment, and one of the major factors that contribute to the pollution of the environment is the inadequate disposal of organic waste. Large parts of the population and establishments pour the oil directly in the kitchen sink and put the fat in pet bottle going to the dumps, there is still no ideal disposal, but there are alternative ways to dispose of it, and one of these means is reuse of the oil soaps. The pH measurement was carried out using the technique Adolfo Lutz (1976) in 10g of sample diluted in distilled water. Cooking oil used to manufacture soap had satisfactory results no caustic soda (ph = 7.11).